Video Assistant Referee's Effect on Football: Turkish Super League Case - Cem Gürler; Volkan Polat (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2021)
Technology is now widely used in sports. One of those technology is video assistant referee (VAR) system. After being officially used in 2018 World Cup for the first time, major leagues started using VAR from the 2018/2019 season. In this study, 94 match weeks played in the Turkey Super League since the 2017/2018 season were analyzed. The present study has two purposes. The first one is to examine the effect of VARs on football statistics. The second purpose is to determine the differences of VAR statistics between two seasons. This study has shown that while goals per game (p<0,05), yellow cards per game, red cards per game was decreased, average match time (second) per game (p<0,05), ball in play time (second) per game was increased after the use of VAR. The second major finding was that the frequency of decisions did not changed per game, and the total count of positions reviewed per game decreased significantly in the second season of VAR system.